Chemical bond deviation in group VI hydrids - Okhrimenko, B.A.; Yushko, O.A.; Yablochkova, K.S. (Functional Materials, 2013)
Ab initio calculations of the chemical bond deviation in molecules were carried out using Gaussian 09 software. The results correlate with the estimations of the deviation angle obtained earlier using experimental data.